UJI EFEKTIFITAS EKSTRAK SAFFRON (CROCCUS SATIVUS) SEBAGAI ALTERNATIF DIAZEPAM TERHADAP HEART RATE PADA TIKUS CIRCADIAN RHYTME SLEEP DISORDER (CRSD) - Suharni, Suharni; Raditya Pangestu; Tania Putri Zulkifli; M. Ferdi Devilito; Ardi Khusnaidi; Afdila Syarfina (Nusantara Hasana Journal, 2024)
Circadian rhythm sleep disorder (CRSD) is a problem that affects people from waking to sleep. There are many ways to reduce the intensity of CRSD; one of them is by taking diazepam. However, the side effects of Diazepam are much more dangerous. Therefore, it is important to use herbal medicines as traditional medicines to maintain health so that they are safe for consumption, one of which is using turmeric (Crocus sativus). This research was conducted at the Pharmacy Laboratory, Universitas Perintis Indonesia. The goal of this study was to compare the average heart rate of rats treated with saffron and diazepam for sleep disorders. Turmeric extract and diazepam were given orally at a dose of 50 mg/KgBB and diazepam at a dose of 0.75 mg/KgBB, and 15 rats were used. Measurement of rats heart rate was carried out on the 1st, 7th, and 14th days. The results of the study concluded that the treatment of experimental animals by presenting saffron and diazepam extracts was able to reduce the average heart rate value in each rats, with data analysis showing that there was a significant difference in the heart rate of each with a value of P = 0.015 (P < 0.05). So it can be said that the use of saffron extract is effective in overcoming CRSD.